Plant parasitic nematode effectors target host defense and nuclear functions to establish feeding cells - Quentin, Michaël; Abad, Pierre; Favery, Bruno (Frontiers in Plant Science, 2013)
Plant parasitic nematodes are microscopic worms, the most damaging species of which have adopted a sedentary lifestyle within their hosts. These obligate endoparasites have a biotrophic relationship with plants, in which they induce the differentiation of root cells into hypertrophied, multinucleate feeding cells. Effectors synthesised in the oesophageal glands of the nematode are injected into the plant cells via the syringe-like stylet and play a key role in manipulating the host machinery. The establishment of specialized feeding cells requires these effectors to modulate many aspects of plant cell morphogenesis and physiology, including defence responses. This cell reprogramming requires changes to host nuclear processes. Some proteins encoded by parasitism genes target host nuclei. Several of these proteins were immunolocalised within feeding cell nuclei or shown to interact with host nuclear proteins. Comparative genomics and functional analyses are gradually revealing the roles of nematode effectors. We describe here these effectors and their hypothesised roles in the unique feeding behaviour of these pests.